A Multiligand Architectural Photosensitizer That Targets Hemagglutinin on Envelope of Influenza Virus for Photodynamic Inactivation. Issue 20 (24th April 2020) - Jeong, Hayoon; Lee, Jeong‐Ju; Lee, Jangsu; Na, Kun
Abstract: The efficacy of current antiviral drugs used to treat influenza has been declining because of mutations and resistance of the virus. Herein, a light‐sensitive multiligand architecture is developed consisting of chitosan conjugated to a photosensitizer and 6'‐sialyllactose (SL) to develop an antiviral agent against influenza with a different mechanism of action (SL‐chitosan‐Chlorin e6, SCC). Saturation transfer difference‐nuclear magnetic resonance determined that the ability of SCC to bind to viral hemagglutinin is stronger than that of the monomeric substance. Virus recognition is confirmed by immunofluorescence and transmission electron microscope imaging. SCC induces viral inactivation by causing permanent membrane damage through its photoactivity. Viral membrane is oxidized by the photoactivity of SCC, thus, the virus membrane collapses. Furthermore, using the plaque reduction assay to evaluate the inhibitory effect of SCC on influenza A and B, it is found that its antiviral effects are 23% and 50% higher than the conventional antiviral drug. Additionally, SCC prevents infection by influenza in 100% of mice subjected to laser irradiation. These results indicate that this photodynamic multiligand structure can overcome the limitations of existing antiviral agents and suggest a pertinent methodology of prophylaxis and treatment by preemptively attacking the virus before it enters the host cell. Abstract : A multiligand architectural photosensitizer that targets hemagglutinin on envelope of influenza virus for photodynamic inactivation is studied. This structure selectively binds to influenza hemagglutinin and the photoactivity of the multivalent ligand structure damages the viral membrane under laser irradiation, resulting in permanent inactivation of the virus. This new strategy simultaneously enables the treatment and prevention of viral infections.